Measures of walkability in the pediatric population: a qualitative review of the literature - Ubiali, A.; Gori, D.; Rochira, A.; Raguzzoni, G.; Fantini, M. P. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Context. Sedentary lifestyle is spreading among children living in urban settings. Recent studies in urban health investigated the effects of built environment on children’s physical activity, focusing on the concept of “walkability”, an index of how much an area is conducive to walking and active transportation. We decided to browse the literature in order to review all possible tools and methods by which walkability has been evaluated and measured.Methods. We conducted a qualitative review of the literature in agreement with PRISMA guidelines, searching three medical databases for papers published between January 1994 and July 2017. Inclusion criteria were: primary studies, population ≤18 years and exposure variable as an assessment of walkability or built environment.Results. We retrieved 1,702 articles and included 195 of them in the final review. Most of the studies were cross-sectional (n=188, 96.4%). We identified two possible approaches and four main tools to address walkability measurement. A subjective method approach was used in 71 studies (36.4%), an objective method in 87 (44.6%). Only 37 studies (19.0%) used both. Main tools were survey (n=70, 35.9%), Geographic Information System (GIS) (n=64, 32.8%), street audits (n=11, 5.6%) and Walk-score™ (n=3, 1.5%). Fortysix studies (23.4%) used mixed methods. Environmental variables’ assessment and definition was found to vary greatly by method of choice Conclusions. We found a high degree of heterogeneity regarding methods and measurements of walkability. A standard approach regarding tools and environmental variables’ choice and definition will be advisable in order to allow comparisons among studies. Also, more longitudinal studies are needed.